Locking Stand-Alone Cage Constructs for the Treatment of Cervical Spine Degenerative Disease - Roberto Alfonso De Leo–Vargas; Ildefonso Muñoz–Romero; Michel Gustavo Mondragón–Soto; Jaime Jesús Martínez–Anda (Asian Spine Journal, 2019)
Study Design Prospective case series study. Purpose Description of the outcome of stand-alone cervical cages for single and multilevel cervical degenerative spine disease. Overview of Literature The aim of anterior cervical discectomy and fusion (ACDF) for cervical spine disease is to improve patient symptoms and spine stability and restore lordosis. Locking stand-alone cages were developed with the goal of minimizing soft tissue disruption anterior to the vertebrae and reducing the profile of the construct by avoiding an anterior plate, thereby maximizing ACDF benefits. Methods This study comprises a case series of patients surgically treated between July 2015 and February 2018 who received single or multilevel ACDF with a zero-profile stand-alone cervical cage. Surgical and clinical preoperative evaluation and surgical outcomes were evaluated using pre- and postoperative Nurick, Visual Analog Scale (VAS), Neck Disability Index (NDI), Japanese Orthopedic Association (JOA) score for myelopathy scales, cervical Cobb angles, postoperative surgical complications, and fusion and subsidence rates. Results Fifty-three patients underwent ACDF; the mean age of these patients was 58.8 years, and their preoperative VAS, NDI, and JOA scores were 8.1, 31.6, and 15.3, respectively. The preoperative Cobb angle was 30.7°. Forty-five percent of patients had one-level, 54.7% had two-level, and 13.2% had three-level procedures. On preoperative magnetic resonance imaging, foraminal stenosis was present in 94.3% of patients, whereas medullar stenosis was present in 41.5%. The rate of complications was 5.7%: two patients had postoperative dysphagia (3.7%), and one patient had a surgical site hematoma. Mean postoperative follow-up time was 6.7 months; postoperative VAS, NDI, and JOA scores were 2.4, 15.9, and 15.8, respectively. Postoperative Cobb angle was 35.9°, fusion rate was 84.9%, and subsidence rate was 11.3%. Conclusions ACDF with zero-profile stand-alone cervical devices is an excellent option for cervical degenerative disc disease of one, two, and three levels, with similar results reported when using ACDF with either cage or plate.